2018
DOI: 10.1037/bar0000101
|View full text |Cite
|
Sign up to set email alerts
|

The experimental analysis of behavior: Whence and thence?

Abstract: This is a personal and idiosyncratic reflection on some areas of the experimental analysis of behavior that have appeared over the last 50 years and that have subsequently been neglected, or relatively neglected. These include stimulus control and divided stimulus control, behavioral ecology, reinforcement for agreement, spatial behavior, training by demonstrating, errorless transfer, punishment and avoidance, and behavioral epigenetics. In my view, revisiting these would pay dividends for the experimental ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…In a recent paper, Davison (2018b) highlighted divided stimulus control as an area that “cries out for future research” (p. 136), and posed the question, “Do divided [stimulus control] effects occur in temporal discriminations?” (p. 136). The present experiment is the first step toward answering this question, and our results tentatively suggest that the answer is “yes,” with the caveat that changes in accuracy were very small in the present experiment, and the effects of relative reinforcer probabilities on divided stimulus control appeared to be time-dependent; such effects appeared greater for the shorter (2 s) interval than for the longer (8 s) interval (see Figure 3).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a recent paper, Davison (2018b) highlighted divided stimulus control as an area that “cries out for future research” (p. 136), and posed the question, “Do divided [stimulus control] effects occur in temporal discriminations?” (p. 136). The present experiment is the first step toward answering this question, and our results tentatively suggest that the answer is “yes,” with the caveat that changes in accuracy were very small in the present experiment, and the effects of relative reinforcer probabilities on divided stimulus control appeared to be time-dependent; such effects appeared greater for the shorter (2 s) interval than for the longer (8 s) interval (see Figure 3).…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies have now shown that relative reinforcer probabilities divide stimulus control, the generality of this relation between relative reinforcer probabilities and divided stimulus control is not well established. One situation in which divided stimulus control, and the variables that determine the division, is presently not well understood is when stimuli provide information about the time of the next reinforcer (Davison, 2018b). That is, if the dimensions of a compound stimulus signal the time of the next reinforcer, rather than whether a left- or right-key response is likely to produce it as in previous studies (e.g., Davison & Elliffe, 2010), do relative reinforcer probabilities determine the division of control between the compound-stimulus dimensions?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Although investigating the effects of relative reinforcer rates on attention allocation has clear theoretical and applied relevance, few studies have done so, and those that have employ similar procedures (Davison, 2018b). Therefore, the generality of the relation between relative reinforcer rates and attention allocation across procedures is not well established.…”
mentioning
confidence: 99%